Factors that affecting work life balance among employees in Human Resource Department of Project Delivery & Technology Division (PD&T) at Petroliam Nasional Berhad (PETRONAS) / Muhammad Noramirulazillah Mohd Rojis - Mohd Rojis, Muhammad Noramirulazillah (Faculty of Business and Management, 2018)
Work life balance are seems to be synonyms for employees and employers. There are many advantages and disadvantages of the policies. However, in academically purpose many seems to ignore the important in achieving the work life balance. This study aims to investigate what are the factors that affecting work life balance among employee in Human Resource Department of Project Delivery & Technology (PD&T) Division at Petroliam Nasional Berhad (PETRONAS). In this study researcher are highlighting four factors (workload, interpersonal relationship, flexible working arrangement, and organization support) that affect work life balance of the employees in the human resource department of PD&T division. This study has been conducted and the data being collected by questionnaires that involved of 92 respondents out of 120 the total population. Sampling technique that been used in this study is simple random sampling. Researcher has conduct reliability test, normality test, correlation analysis and regression analysis in this study. All the variable in this study has meet the acceptable Cronbach Alpha that must be above 0.60. Result of normality analysis that has been interpreted shows that all the variable are normal and within the range. For correlation analysis revealed that all the variable are interrelated and it can be used for the next test. Lastly, researcher has conduct regression test in order to determine the hypothesis testing and the most influential factors in this study. The most influential factors in this study is organizational support ( β = 0.328, p = 0.002). there are four hypotheses that been developed for this study and there is two hypotheses that been accepted which is Hypothesis 1 and 2. Researcher also suggest a few of recommendation in order to improve the study and for the future research researcher are highlighting a several factors that can contribute in affecting of employees work life balance.